(untitled) (Dhaka University Journal of Science, 2022)
The rapid rise of diabetes, cardiovascular disease (CVD) and chronic respiratory disease (CRD) are causing serious challenges for Bangladesh to achieve the sustainable development goal (SDG) target 3.4 by 2030. The study aims to describe the state of healthcare facilities to provide diagnosis and treatment for diabetes, CVD and CRD related services in Bangladesh. This cross-sectional study used data from 2017 Bangladesh Health Facility Survey (BHFS). A total of 406 health facilities providing all three services were considered for this study. Findings of the study illustrated that there were rural-urban disparities in healthcare facilities to provide diabetics, CVD, CRD related services. Diabetics and CRD related services were significantly higher in public healthcare facilities of urban areas compared to rural areas (P <0.008 and P<0.001, respectively). Also, public health facilities of urban areas were more likely to provide CVD related services compared to rural areas. While private healthcare facilities of urban areas were more likely to provide CVD, CRD related services than rural areas. Private healthcare facilities of rural areas were in better condition to provide diabetes related services than urban areas. However, the country is yet to attain optimal progress in the overall status of health sector. Therefore, in order to cope up with the rising burden of diabetes, CVD and CRD and to minimize the burden of disease specific outof pocket healthcare expenses, recommendations include strengthening and improving stewardship, improving quality of services and improving monitoring as well as supervision of decentralized healthcare facilities. Dhaka Univ. J. Sci. 70(1): 14-21, 2022 (January)